Rise of Brandenburg-Prussia, 1618-1740. - Shennan, Margaret (Routledge, 1995)
Incorporating international and domestic relations and economic and cultural influences, Shennan surveys the rise of Prussia from the early 17th century to 1740, highlighting and evaluating the role of its rulers and their idiosyncracies.